Surgical Management of the Cesarean Scar Ectopic Pregnancy: A Case Report. (22nd December 2013) - Nankali, Anisodowleh; Ataee, Mina; Shahlazadeh, Haleh; Daeichin, Sara
Abstract : Cesarean scar pregnancy is one of the rarest forms of ectopic pregnancy. Little is known about its incidence and natural history. The diagnosis and treatment of cesarean scar pregnancy (CSP) is challenging. The authors reported here a case of cesarean scar pregnancy (CSP) with hypovolemic shock that underwent emergency laparotomy with resection of ectopic mass. The patient was discharged from the hospital without any complications.